Urgensi Pelaksanaan Kebebasan Berkontrak dalam Merumuskan Perjanjian Guna Mewujudkan Keadilan Bagi Para Pihak - Putri Nabila, Andita; Djayaputra, Gunawan (Universitas Ekasakti, 2023)
The principle of freedom of contract is a principle that is used as the basis for the existence of standard contracts in regulating legal relations between business actors and consumers, but the application of this principle requires that the parties to the contract have a balanced position so that the rights and obligations, provisions in the contract can accommodate all interests. the parties. Freedom of contract is an essential legal aspect of individual freedom. In its development, it turns out that freedom of contract can bring injustice because this principle can only achieve its goal, namely bringing optimal welfare as possible if the parties have balanced bargaining power. In reality, this often does not happen so the state considers it necessary to intervene to protect the weak party. The imbalance in the position of business actorsa and consumers causes the provisions in standard agreements to be more profitable for business actors and detrimental to consumers. Therefore, it is necessary to limit the application of the principle of freedom of contract in standard contracts by enforcing regulations that prohibit certain clauses from being included in standard contracts, as well as monitoring the use of standard contracts in business activities.